How buildings work the natural order of architecture - Allen, Edward 1938- (Oxford University Press, 2005)
Illustrated with many line drawings, this guide provides information on a building's function: how it stands up, keeps its occupants safe and comfortable, gets built, grows old, and dies - and why some buildings do this so much better than others. It is intended for architects, superintendents, and students of architecture and construction